Enteric Conversion of Bladder-drained Pancreas as a Predictor of Outcomes in Almost 600 Recipients at a Single Center. Issue 5 (May 2020) - Riad, Samy M.; Keys, Daniel O.; Jackson, Scott; Vakil, Viral; Berglund, Danielle; Matas, Arthur; Finger, Erik B.; Kandaswamy, Raja
Abstract : Background: Complications associated with bladder-drained pancreata necessitating enteric conversion are common. Data on the outcomes after enteric conversion are conflicting. We studied the association between enteric conversion and the pancreas graft rejection, loss, and mortality. Methods: At our center, 1117 pancreas transplants were performed between 2000 and 2016. We analyzed 593 recipients with bladder-drained pancreata, of which 523 received solitary transplants and 70 received simultaneous pancreas-kidney transplants. Kaplan-Meier function was used to estimate time to conversion by transplant type. Cox proportional hazards models were utilized to evaluate patient survival, death-censored graft survival, and acute rejection-free survival while treating conversion as a time-dependent covariate. Subsequently, we examined the association between timing of conversion and the same outcomes in the conversion cohort. Results: At 10 y posttransplant, 48.8% of the solitary pancreas recipients and 44.3% of simultaneous pancreas-kidney transplant recipients had undergone enteric conversion. The enteric conversion was associated with 85% increased risk of acute rejection (hazard ratio [HR] = 1.85; 95% confidence interval [CI] = 1.37-2.49; P < 0.001). However, the conversion was not associated with graft loss or mortality. In the conversion cohort, a longer interval from engraftment to conversion was associated with an 18% lower rejection rate (HR = 0.82; 95% CI = 0.708-0.960; P = 0.013) and a 22% better graft survival (HR = 0.78; 95% CI = 0.646-0.946; P = 0.01). Conclusions: Enteric conversion was associated with increased risk of rejection, but not increased risks of graft loss or mortality. The decision to convert should consider the increased rejection risk. A longer interval from engraftment to conversion appears favorable.